Dystonias: rehabilitation - Almeida, Tatiane Lopes Teixeira; Falkenburg, Lilian; Gianni, Maria Angela de Campos; Lourenção, Maria Inês Paes; Nacarato, Maria Inês; Pedroso, Tatiana Domingues; Terranova, Thaís Tavares; Nunes, Lucas Martins de Exel; Rosa, Chennyfer Dobbins Paes da; Imamura, Marta; Battistella, Linamara Rizzo (Acta Fisiátrica, 2013)
Articles in the MedLine (PubMed) database and other research sources were reviewed, with no time limit. The search strategy used was based on structured questions in the PICO format from the initials: Patient, Intervention, Control and Outcome. The descriptors used were: dystonia and (benzodiazepines or baclofen or tizanidine or clodinine): dystonia and (anticholinergics or haloperidol or lisuride); dystonia and (botulinum toxin); dystonia cervical and (speech therapy or speech pathologist or botulinum toxin); focal dystonia and (botulinum toxin); dystonia and (sensory stimulation or sensory rehabilitation); dystonia and (biofeedback or electromyography biofeedback); dystonia and (transcranial magnetic stimulation); (dystonic disorders or dystonia) and (self help devices or assistive technology or assistive technologies or rehabilitation); dystonia and (activity daily living); dystonias and (neurosurgery not intrathecal baclofen).